Development, characterization and solubility study of solid dispersions of cefuroxime axetil by the solvent evaporation method - S C Arora; P K Sharma; Raghuveer Irchhaiya; Anurag Khatkar; Neeraj Singh; Jagbir Gagoria (Wolters Kluwer Medknow Publications, 2010)
Cefuroxime Axetil (Poorly water soluble drug), when prepared as solid dispersion showed improved solubility and dissolution. Therefore, the main purpose of this investigation was to increase the solubility and dissolution rate of Cefuroxime Axetil by the preparation of its solid dispersion with urea, using the solvent evaporation method. Physical mixtures and solid dispersions of Cefuroxime Axetil were prepared by using urea as a water-soluble carrier in various proportions (1:1, 1:2, 1:3, 1:4, 1:5, 1:6, and 1:7 by weight), by employing the solvent evaporation method. The drug release profile was studied and it was found that the dissolution rate and the dissolution parameters of the drug from the physical mixture as well as solid dispersion were higher than those of the intact drug. The Fourier Transform Infrared (FTIR) spectra revealed no chemical incompatibility between the drug and urea. Drug-polymer interactions were investigated using differential scanning calorimetry (DSC) and Powder X-Ray Diffraction (PXRD).